Hybrid cobalt-based electrocatalysts with adjustable compositions for electrochemical water splitting derived from Co2+-Loaded MIL-53(Fe) particles. (1st October 2018) - Wang, Jingyun; Cui, Cao; Lin, Rongbin; Xu, Chunhui; Wang, Jin; Li, Zhengquan
Abstract: Composite Co-based electrocatalysts exhibit synergetic electrochemical performance and play important role in water-splitting devices. Previous MOF-template route to targeting Co-electrocatalysts relies mainly on regular Co-MOFs particles, and how to obtain hybrid Co-electrocatalysts with adjustable compositions is still challenging. Here we present a facile route to obtain hybrid Co-electrocatalysts with tunable compositions by impregnating different amount of Co 2+ ions in common Fe-MOF particles followed by a calcination process. Four different Co-based electrocatalysts with regular porous structures have been developed and their OER activities are investigated. Among them, metallic Co-containing composite electrocatalysts (Co/CoO/CoFe2 O4 ) exhibit both HER and OER activity, and they are applicable to overall water splitting. This work shares a new strategy to achieve porous Co-based composite electrocatalysts and a simple route to tailor their compositions and activities.